Lungworms and gastrointestinal parasites of domestic cats: a European perspective. Issue 9 (August 2017) - Giannelli, Alessio; Capelli, Gioia; Joachim, Anja; Hinney, Barbara; Losson, Bertrand; Kirkova, Zvezdelina; René-Martellet, Magalie; Papadopoulos, Elias; Farkas, Róbert; Napoli, Ettore; Brianti, Emanuele; Tamponi, Claudia; et al.
Graphical abstract: Highlights: The occurrence of feline lungworms in 12 European countries was assessed. Cats were screened and treated for lungworms and gastrointestinal parasites. Lungworms were morphologically and molecularly identified. Aelurostrongylus abstrusus, Troglostrongylus brevior, Eucoleus aerophilus and Oslerus rostratus infections were diagnosed. About one in 10 cats is at risk of lungworm infection in Europe. Abstract: With the exception of Aelurostrongylus abstrusus, feline lungworms have been poorly studied. Information on their distribution is patchy and mostly limited to case reports. In this study, the occurrence of feline lungworms and co-infecting gastrointestinal parasites has been investigated in 12 European countries (i.e. Austria, Belgium, Bulgaria, France, Greece, Hungary, Italy, Portugal, Romania, Spain, Switzerland and the United Kingdom). An average of 10 domestic cats, with regular outdoor access, was sampled each month for 12 months, and freshly passed faeces were collected. Stools were processed using a McMaster assay and a quantitative Baermann-Wetzel method. Animals positive for lungworms and/or gastrointestinal parasites were treated with a formulation containing fipronil, ( S )-methoprene, eprinomectin, and praziquantel (Broadline®, Merial), and re-sampled 28 days post-treatment. The association between lungworm infection and risk factors was analysed using statistical medians/means and the efficacy of the treatment against each lungworm species was assessed. Of 1990 cats sampled, 613 (30.8%) were positive for at least one parasite, while 210 (10.6%) were infected by lungworms. The prevalence of lungworm infection varied between the sampled sites, with the highest recorded in Bulgaria (35.8%) and the lowest in Switzerland (0.8%). None of the cats from Austria or the United Kingdom were infected by lungworms. Aelurostrongylus abstrusus was the species most frequently detected (78.1%), followed by Troglostrongylus brevior (19.5%), Eucoleus aerophilus (14.8%) and Oslerus rostratus (3.8%). The overall efficacy of the treatment was 99% for A. abstrusus and 100% for T. brevior, O. rostratus and E. aerophilus . Data presented provide a comprehensive account of the diagnosis, epidemiology and treatment of feline lungworms in Europe, as well as of the occurrence of co-infections by gastrointestinal parasites.